Vitamin status in morbidly obese patients: a cross-sectional study - Aasheim, Erlend T; Hofsø, Dag; Hjelmesæth, Jøran; Birkeland, Kåre I; Bøhmer, Thomas (The American journal of clinical nutrition, 2008)
BACKGROUND:Morbid obesity is associated with low circulating concentrations of 25-hydroxyvitamin D. Few data on the concentrations of other vitamins in morbidly obese patients are available. OBJECTIVE:The objective was to compare serum and blood vitamin concentrations in morbidly obese patients with those in healthy subjects. DESIGN:In 2 public hospital departments (southeast Norway), we prospectively examined 110 consecutive patients (76 women) and 58 healthy controls (30 women) not taking multivitamin supplements. Patients and controls did not differ significantly in age or ethnicity. The mean (±SD) body mass index (in kg/m²) was 45 ± 7 in the patients and was 24 ± 3 in the controls. Patients with vitamin concentrations lower than 2 SD below the sex-specific mean in controls were considered to have inadequate vitamin status. RESULTS:The morbidly obese women and men had significantly lower concentrations of vitamin B-6, vitamin C, 25-hydroxyvitamin D, and lipid-standardized vitamin E than did the healthy controls (P < 0.01 for each). The status of these vitamins was inadequate in a substantial proportion of the patients (11-38%). The status of vitamins A, B-1, B-2, and B-12 and of folic acid was adequate in most of the patients (95-100%). A moderately elevated C-reactive protein concentration was associated with lower vitamin A, B-6, and C concentrations. In a multiple regression analysis, concentrations of alkaline phosphatase (inverse relation) and vitamin C were the strongest determinants of serum vitamin B-6 concentrations. CONCLUSIONS:Low concentrations of vitamin B-6, vitamin C, 25-hydroxyvitamin D, and vitamin E adjusted for lipids are prevalent in morbidly obese Norwegian patients seeking weight-loss treatment.